Effect of rough walls on hydraulic jump in arectangular open channel and appreciate experimental and theoretical analysis - Abdelouahed Brahimi; Zina Mansouri (International Journal of Computational and Experimental Science and Engineering, 2026)
Hydraulic jumps have been attracted to many researchers for a long period of time because of its importance in designing hydraulic structures. Stilling basins are one of the possible solutions for hydraulic jump to dissipate kinetic energy to produce safe downstream flow, which causes no bed scour and bank erosion. Generally, the dimension of a hydraulic jump is taken as an indicator of the dimension of the stilling basin or as a design parameter. Lot of study has been made on hydraulic jump, and very limited studies have been reported in literature on the performance of hydraulic jumps formed in rectangular channel with rough walls, that way the paper is a valuable contribution to the subject. The purpose of the research work was to observe the phenomenon of the hydraulic jump,and to develop an understanding of the effect of roughness in an open horizontal channel. Also, to appreciate therelationship between the experimental results and the theoretical analysis based on the application of continuityand momentum principles. A series of experiments were carried out in a rectangular flume which consists of artificially roughenedwalls formed by circular balls with homogeneous and uniform shapes. The hydraulic jump parameters such as, pre jump depth, post jump depthand flow rate were measured for different roughness. During this study, sixty experimental runs were conducted by varying the Froude number, ranging from 2 to 17. It carries out on four sluice gate opening (h1 = 2, 3, 4 and 5 cm) with four different roughness elements of diameters (ε = 6, 8, 10 and 12mm) were introduced throughout the length of channel. The hydraulic jump considered in the present work have been controlled by sill with thirteen different sizes varying between 3 to 15 mm. The analysis of experimental data showed that the rough walls reduce the conjugate depthratiothan those on smooth walls. They have also, this parameter vary linearly with the Froude number and roughness where as other hydraulic jump characteristics are not. The analytical equation for the conjugate depthsratio as given byapplied theoretical the momentum equation, and itisadjusted well with the experimental data.Itis satisfactory for predicting the conjugate depth ratio of hydraulic jump on rough walls.